2009
DOI: 10.1179/016164109x12445505689643
|View full text |Cite
|
Sign up to set email alerts
|

Stroke and dementia

Abstract: Vascular dementia causes dependence and disability. Most stroke survivors show improvement, but many develop dementia. Understanding for vascular dementia has recently improved, leading to improved treatment planning. Further research, especially on treatment for vascular dementia, is greatly needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 27 publications
1
45
2
Order By: Relevance
“…Cerebral ischemic injury resulting from either focal or global circulatory arrests in the brain, is one of the major causes of death and disability in adults (Pinkston et al, 2009). Global cerebral ischemia is a clinical outcome occurring as a consequence of cardiac arrest, reversible severe hypotension or other situations that deprive the brain of oxygen and glucose (Nedergaard and Diemer, 1988;White et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral ischemic injury resulting from either focal or global circulatory arrests in the brain, is one of the major causes of death and disability in adults (Pinkston et al, 2009). Global cerebral ischemia is a clinical outcome occurring as a consequence of cardiac arrest, reversible severe hypotension or other situations that deprive the brain of oxygen and glucose (Nedergaard and Diemer, 1988;White et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Another ambiguous question emerges: Where does the earliest process or do the processes leading to dementia initially begin? AD patients demonstrate neurodegenerative pathology in temporal lobe (disturbances in language) with diagnosed AD dementia [8]. It has been suggested that the primary event of neurodegenerative pathology in AD starts in the medial temporal lobe and proceeds to entorhinal cortex and hippocampus [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary, genetic and molecular factors are important determinants in progression and treatment of the above diseases [1,[47][48][49][50][51]53]. In developed countries ischemic stroke is a major cause of physical disability, the third leading cause of mortality and the second most common cause of dementia [28,41]. In a population of 1 million people 2.4 thousand individuals will have a stroke each year, of whom less than 50% will be independent 1 year later [28].…”
Section: Introductionmentioning
confidence: 99%
“…Age-related disorders such as Alzheimer's disease and brain ischemia represent a major clinical problem in developed countries [18,28,41] and are a major economic burden for health care systems [15,37]. Dietary, genetic and molecular factors are important determinants in progression and treatment of the above diseases [1,[47][48][49][50][51]53].…”
Section: Introductionmentioning
confidence: 99%